How pulmonary function changes after pectus excavatum correction surgery - (:unkn) unknown (SAGE Publications Inc., 2015)
Aim We aimed to determine the effects of minimally invasive repair of pectus excavatum on pulmonary function and quality of life. Methods Minimally invasive pectus excavatum repair was undertaken in 80 patients with a mean age of 16.91"‰±"‰4.37 years (range 7-30 years) and a mean Haller index of 4.07"‰±"‰1.39; 85% of the patients were male. They and their parents completed the Nuss Questionnaire Modified for Adults, and pulmonary function tests were performed on the patients before and 6 months after the operation. Results The mean Nuss score was 31.06"‰±"‰6.78 before the operation and it increased to 37.1"‰±"‰8.31 (p"‰="‰0.000) 6 months after the operation. Forced vital capacity decreased from 3.70"‰±"‰1.23 to 3.48"‰±"‰1.03"‰L (p"‰="‰0.05) postoperatively. The percentage of expected forced vital capacity decreased from 83.21%"‰±"‰16.97% to 76.52%"‰±"‰20.98% (p"‰="‰0.01). There was no significant change in forced expiratory volume in 1"‰s. The mean ratio of forced expiratory volume in 1"‰s to forced vital capacity was 86% preoperatively and it increased to 91% postoperatively (p"‰="‰0.000). Conclusions Minimally invasive pectus excavatum repair has a positive impact on the quality of life of pectus excavatum patients, but a negative impact on forced vital capacity. Follow-up studies are needed to assess the long-term changes in pulmonary function after this operation. © The Author(s) 2014.
Keywords: Body image; Funnel chest; Minimally invasive surgical procedures; Patient satisfaction; Quality of life; Respiratory function tests